Reorganization of Moscow Divisions of People's Militia into Rifle Ones in August - September 1941 - Alexey Yurievich Bezugolny (RUDN Journal of Russian History)
Through their article, the author considers the features of the organizational and staff structure and combat training of 12 divisions of people's militia of Moscow during the summer and autumn of 1941. The research is based on archival sources, most of them are introduced into scientific use for the first time: documents of management and record keeping of the Moscow Military District and the Reserve Front, accounting and statistical materials of the highest military authorities, and an array of documents of the Commission on the History of the Great Patriotic War from the Academy of Sciences of the USSR. The documents show that shortcomings revealed already during the first field exercises, such as the inadequacy of some personnel for the requirements of combat service, low qualifications of the command staff, diversity of small arms and artillery weapons, poor rear service of divisions, etc., were in fact a common occurrence. These issues required a significant reorganization of the divisions of people's militia. Eventually, all the divisions of people's militia were reorganized into regular infantry divisions of the Red Army and entered battle in this status in early October 1941. The author also follows the process and results of this reorganization.